Caracterização morfológica e molecular de genótipos de tomateiro do banco ativo de germoplasma da UTFPR - Pato Branco - Kutz, Talita Slota (2018)
In plant breeding, variability is critical in choosing the parents. In contrast, when compared to other species of the genus Solanum, the tomato has a narrow genetic base. Currently, in the southwestern region of Paraná there is a lack of openpollinated tomato cultivars adapted to the region and agroecological cultivation. Thus, the objective of this work was to characterize the morphological and molecular variability of the open – pollinated tomato genotypes of BAGT UTFPR – Pato Branco. The experiment was conducted in the Experimental Area of UTFPR – Pato Branco Campus, in a randomized block design, with four replications. The morphological characterization was performed in 17 genotypes, from 41 quantitative and qualitative descriptors of fruit and plant, evaluation of diseases and pests and physical-chemical analyzes of fruits. The molecular variability was analyzed by means of 20 SSR primers in 19 tomato genotypes. The data were submitted to different multivariate analyzes. In the characterization of fruit quality, 76.44% of the variability was composed by the chromatic descriptors b * (44.43%) and L * (7.21%), pedicel scar diameter (16.78%), number of loci (8.02%) and fruit length (8.02%). The general morphological average dissimilarity among the genotypes was considered low, the values found for the groupings based on the quantitative plant characters were 0.34, 0.32 for the fruits and for the general characters 0.33. Ten of the 20 primers that showed visible bands had PIC above 0.58. The average similarity obtained from polymorphic fragments amplified through SSR primers was 0.72. The commercial GA genotype is morphologically and genetically similar to the UTFPR_046 genotype. UTFPR_016 and UTFPR_029 presented 90% genetic similarity and were allocated in the same cluster in all morphological analyzes, indicating a high degree of kinship among these materials. The yellow-orange fruit genotypes, UTFPR_008 and UTFPR_015, are morphologically similar, however, genetically they are 41% divergent. The mean morphological dissimilarity (0.33) was very close to the molecular (0.28). Morphological and molecular analyzes allowed the identification of clusters with characteristics of interest and the existence or not of duplicity in BAGT UTFPR – Pato Branco. The results of this work contributed to the formation and characterization of UTFPR – Pato Branco BAGT and may help in the genetic improvement of open pollinated tomato varieties for agroecological cultivation in the southwestern region of Paraná.